Impact of corrosion on mechanical properties of additively manufactured Invar 36. Issue 3 (14th March 2022) - Heine, B.; Kah, A.; Sedlmajer, M.; Ocker, C.; Merkel, M.
Abstract: Invar alloys are used for high‐precision applications due to their invariance of the coefficient of thermal expansion over a temperature range up to about 250 °C. The present study determines the mechanical and corrosive properties of Invar 36 (64 % Iron – 36 % Nickel) specimens produced by laser powder bed fusion. Tensile specimens were fabricated to investigate the mechanical properties. The influence of a horizontal and vertical building orientation is considered. An apparent mechanical anisotropy depending on the respective building is observed. Based on this, further tensile specimens were stored in a hydrochloric acid pickling solution, a sulphate buffer solution and a sodium chloride solution to analyse the corrosion behaviour. The findings after eight weeks in the individual media show that outsourcing the Invar 36 specimens in a sulphate buffer solution results in significant changes in the mechanical properties, especially fracture elongation. Abstract : Additively manufactured Invar 36 is exposed in a hydrochloric acid pickling solution, a sulphate buffer solution and a sodium chloride solution. The corrosion behaviour and the resulting mechanical properties are analysed. Translation abstract: Invar‐Legierungen werden aufgrund ihrer Invarianz des Wärmeausdehnungskoeffizienten über einen Temperaturbereich von bis zu etwa 250 °C für Hochpräzisionsanwendungen verwendet. In der vorliegenden Studie werden die mechanischen und korrosiven Eigenschaften von Invar 36 (64 % Eisen – 36 % Nickel) Proben bestimmt, die durch Pulverbett basiertes Laserstrahlschmelzen hergestellt wurden. Zur Untersuchung der mechanischen Eigenschaften wurden Zugproben angefertigt. Der Einfluss einer horizontalen und vertikalen Baurichtung wird berücksichtigt. Es wurde eine mechanische Anisotropie in Abhängigkeit von der jeweiligen Bauweise festgestellt. Darauf aufbauend wurden weitere Zugproben in einer Salzsäurebeizlösung, einer Sulfatpufferlösung und einer Natriumchloridlösung gelagert, um das Korrosionsverhalten zu analysieren. Die Ergebnisse nach acht Wochen in den einzelnen Medien zeigen, dass die Auslagerung der Invar 36‐Proben in einer Sulfatpufferlösung zu deutlichen Veränderungen der mechanischen Eigenschaften, insbesondere der Bruchdehnung, führt.